Conceptual control across modalities: graded specialisation for pictures and words in inferior frontal and posterior temporal cortex. (September 2015) - Krieger-Redwood, Katya; Teige, Catarina; Davey, James; Hymers, Mark; Jefferies, Elizabeth
Abstract: Controlled semantic retrieval to words elicits co-activation of inferior frontal (IFG) and left posterior temporal cortex (pMTG), but research has not yet established (i) the distinct contributions of these regions or (ii) whether the same processes are recruited for non-verbal stimuli. Words have relatively flexible meanings – as a consequence, identifying the context that links two specific words is relatively demanding. In contrast, pictures are richer stimuli and their precise meaning is better specified by their visible features – however, not all of these features will be relevant to uncovering a given association, tapping selection/inhibition processes. To explore potential differences across modalities, we took a commonly-used manipulation of controlled retrieval demands, namely the identification of weak vs. strong associations, and compared word and picture versions. There were 4 key findings: (1) Regions of interest (ROIs) in posterior IFG (BA44) showed graded effects of modality (e.g., words>pictures in left BA44; pictures>words in right BA44). (2) An equivalent response was observed in left mid-IFG (BA45) across modalities, consistent with the multimodal semantic control deficits that typically follow LIFG lesions. (3) The anterior IFG (BA47) ROI showed a stronger response to verbal than pictorial associations, potentially reflecting a role for this region in establishing a meaningful context that can be used to direct semantic retrieval. (4) The left pMTG ROI also responded to difficulty across modalities yet showed a stronger response overall to verbal stimuli, helping to reconcile two distinct literatures that have implicated this site in semantic control and lexical-semantic access respectively. We propose that left anterior IFG and pMTG work together to maintain a meaningful context that shapes ongoing semantic processing, and that this process is more strongly taxed by word than picture associations. Highlights: One of the first studies of semantic control across verbal and non-verbal modalities. Left mid-IFG supports controlled semantic retrieval for both words and pictures. Left and right posterior IFG show graded modality effects. Left anterior IFG and pMTG respond more to verbal than pictorial associations. Co-activation of these sites may maintain a context to shape semantic processing.